Herbarium Apenninicum (APP): An Archive of Vascular Plants from Central Italy - Fabio Conti; Giacomo Cangelmi; Jamila Da Valle; Fabrizio Bartolucci (Diversity, 2024)
The Herbarium Apenninicum (international code: APP), hosted in the Floristic Research Center of the Apennines (Abruzzo, central Italy), is approximately composed of about 80,000 specimens of vascular plants; 66,352 of them are mounted with data labels and entered in a database. The specimens from the Abruzzo administrative region (central Italy) correspond to more than half of the collection (57.8% of the specimens), while immediately afterwards, other neighboring provinces of central Italy follow. Outside of Italy, the most represented areas are Morocco and southern European countries. Most of the specimens were collected between 2001 and 2020; nevertheless, the herbarium also contains two historical collections from the end of the nineteenth century to the beginning of the twentieth century. The herbarium houses 146 types.